1994
DOI: 10.1128/iai.62.4.1400-1405.1994
|View full text |Cite
|
Sign up to set email alerts
|

Production of antibodies to antigens of Candida albicans in CBA/H mice

Abstract: Reported targets of the specific immune responses to Candida albicans in human candidiasis include a 47-kDa breakdown product of a 90-kDa heat shock protein (HSP 90) (R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…HSP70s play an important immunologic role in a variety of infections, such as malaria (2), trypanosomiasis (16), bilharziasis (23), leishmaniasis (34), and diseases caused by chlamydiae (5,9,31,51) and mycobacteria (15,44). The involvement of HSP90 in fungal infections such as candidiasis has also been described (8), while HSP88 is involved in aspergillosis (6). Furthermore, a member of the HSP70 family of Histoplasma capsulatum was recognized as a target of cell-mediated, protective immunity (17).…”
Section: Discussionmentioning
confidence: 99%
“…HSP70s play an important immunologic role in a variety of infections, such as malaria (2), trypanosomiasis (16), bilharziasis (23), leishmaniasis (34), and diseases caused by chlamydiae (5,9,31,51) and mycobacteria (15,44). The involvement of HSP90 in fungal infections such as candidiasis has also been described (8), while HSP88 is involved in aspergillosis (6). Furthermore, a member of the HSP70 family of Histoplasma capsulatum was recognized as a target of cell-mediated, protective immunity (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the nonconservative substitutions were between amino acids 557-644, which was perceived as an area key to the antigenicity of the molecule (La Valle et al, 1995). Immunization with a recombinant of this molecule produced a murine antibody response against bands at 70 kDa, which were suggested as similar to a 75-kDa hsp shown previously as immunodominant in CBA/H mice during systemic candidiasis (Costantino et al, 1994). Immunoscreening a mycelial expression library further identified a sequence which was 99.3% identical to C. albicans HSP70 and approximately 79% identical to the sequences of SSA1-4 (Eroles et al, 1995).…”
Section: Hsp70mentioning
confidence: 91%
“…Other hsps have been identified by growing C. albicans at 42 1C. Induced bands on electrophoresis were visible at 28, 38, 47 and 60 kDa, although the predominant response was in the 70-110-kDa range (Franklyn & Warmington, 1994). Two-dimensional electrophoresis of extracts of C. albicans identified homologues of S. cerevisiae hsp90, Ssa1, Ssa4, Ssb1/Kar2, Ss31/ Pdr13 and hsp104 .…”
Section: Hsps and Pathogenic Fungi Candida Albicansmentioning
confidence: 99%
See 1 more Smart Citation
“…hsp70 is also recognized by sera of patients with oral and esophageal infection (524). It has also been demonstrated that the antibody response in a murine model of systemic candidiasis includes reactivity against a 75-kDa hsp (85). Due to the high levels of homology between the different hsp70s, a combination of antibodies to the different members of this family in C. albicans as well as to hsp70s from other microorganisms may be present in the host serum.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%